A healthcare-driven framework for facilitating the secure sharing of data across organisational boundaries. - Simpson, A; Power, D; Russell, D; Slaymaker, M; Kouadri Mostefaoui, G; Ma, X; Wilson, G (2008)
We report upon the development of sif (for service-oriented interoperability framework), a platform that has been developed to support the secure aggregation of medical data from disparate sources. By taking a data-agnostic approach to data access and transfer, sif provides a generic interface to data sources, which allows the current version to expose data from any relational database and any file system in a secure fashion. Application developers may then access and utilise such data via a simple API. sif is being developed within the GIMI (Generic Infrastructure for Medical Informatics) project; as such, we discuss its various applications within that context.